2007
DOI: 10.1111/j.1600-6143.2007.01932.x
|View full text |Cite
|
Sign up to set email alerts
|

The Medical Evaluation of Living Kidney Donors: A Survey of US Transplant Centers

Abstract: There are no conflicts of interest to report.The use of living donors for kidney transplantation in the United States is common, and long-term studies have demonstrated the safety of donation by young, healthy individuals. However, transplant programs have little data to guide them in deciding which donors are unacceptable, and which characteristics are associated with kidney disease or poor psychosocial outcomes after donation. To document current practices in evaluating potential donors, we surveyed all US k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
295
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(306 citation statements)
references
References 31 publications
4
295
1
2
Order By: Relevance
“…A quarter of programs exclude patients with a history of renal stones, while another quarter accept these patients without requiring a metabolic workup. 3 Our study results should be generalizable because our acceptance criteria are similar to many other programs.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…A quarter of programs exclude patients with a history of renal stones, while another quarter accept these patients without requiring a metabolic workup. 3 Our study results should be generalizable because our acceptance criteria are similar to many other programs.…”
Section: Discussionmentioning
confidence: 96%
“…A 2007 survey of transplant centres demonstrated that older, more obese, hypertensive and non-related patients are more likely to be accepted as donors compared to the previous decade. [3][4][5] Long-term health outcomes for extended-criteria donors are less clear. 4 In an attempt to make the donor screening process consistent, several consensus statements outlining the medical and psychosocial evaluation exist.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some countries, as shown in the Norwegian registry, 16% of living donors are older than 60 years, and 7.7% are over the age of 65, whereas in Canada 6% of donors are older than 60 years [18,19]. The American RDS shows no upper age limits regarding acceptance of donors [20]. The results obtained in the recent analysis of United Network for Organ Sharing (UNOS) database from 1994 to 2012 that made comparison of living donors >60 years, living donors <60 years, showed equal graft survival and overall survival in older donors compared to SCD (standard criteria donor), better than ECD (expanded criteria donor), but worse than grafts obtained from younger living donors [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Historiquement, les pionniers de la transplan-plus largement à des donneurs qualifiés de « marginaux », c'est-à-dire déjà hypertendus, voire ayant une protéinurie minime. Nous manquons de données à long terme concernant ces cas et l'établissement de registres de suivi des donneurs semble indispensable, tant pour répondre à ces interrogations que pour proposer aux donneurs le suivi médical approprié dont ils pourraient avoir besoin [11]. Il ne s'agit en aucun cas de considérer les donneurs comme des malades mais de leur proposer une stratégie de dépistage et de prévention.…”
Section: éPidémiologieunclassified